A velhice em uma dimensão existencial: perspectivas entre sentido de vida, religiosidade, vitalidade e temporalidade - Vieira, Danielly Costa Roque (2014)
The present study aimed to identify associations between religiosity, the perception of the meaning of life, the ontological perception of time and subjective vitality of older people. An empirical study was conducted with hundred people with an average age of 67.2 years (SD = 5.6) and range 60-87 years. The participants responded to a battery of four instruments: Religious Attitudes Scale (RAS), Sense of Life Questionnaire (QSL), Perception Scale Ontology of Time (EPOT) and the Subjective Vitality Scale (EVS) along with those instruments was added an instrument to measure the socio-demographic data such as age, gender, education and religion. It was observed knowledge and religious behavior are directly associated with the realization of meaning of life. Concerning the Subjective Vitality, this was directly associated with the ontological perception of the past. The results were discussed in light of the existential analysis of Viktor Frankl.